Characteristics of the Social Commerce Environment and the Formation of Purchase Intention: A Study on Tiktok Shop Users - Nilam Basuki; Raden Roro Ratna Roostika (COMMICAST, 2026)
The development of the digital economy has changed people's consumption patterns from conventional models to technology-based platforms, especially through the integration of social media and trading activities known as social commerce. TikTok Shop as one of the leading social commerce platforms in Indonesia presents challenges in understanding the mechanism of forming consumer purchase intent through the characteristics of the digital environment and the social interactions created in it. This study aims to analyze the influence of social commerce environmental characteristics on purchase intent by considering the mediating role of interpersonal interaction and perceived value of customers. This research contributes to the development of an integrative model that explains the complex mechanism of buying intention formation in the context of live streaming-based social commerce. The research method used a quantitative approach with a causal design involving 200 respondents who were active users of TikTok Shop in Indonesia. Data collection was carried out through an online questionnaire with a six-point Likert scale, then analyzed using Partial Least Square-Structural Equation Modeling. The theoretical framework adopts the Stimulus-Organism-Response model to explain the causal relationships between constructs. The results showed that the characteristics of the social commerce environment had a significant effect on interpersonal interaction (β=0.525; p<0.05), interpersonal interaction had a significant effect on the perceived value of customers (β=0.639; p<0.05), the value perceived by customers had a significant effect on purchase intention (β=0.579; p<0.05), and there was a direct influence of environmental characteristics on purchase intention (β=0.282; p<0.05). The research model was able to explain the variance in purchase intent by 61.5 percent, confirming that all hypotheses were accepted with a strong level of significance. The findings confirm that an interactive platform environment that supports socialization effectively shapes purchase intent through social interaction mechanisms and value creation for consumers.